The Critical Analysis of Competence Development of Head of State Madrasah - Saiful Mujab (Ilomata International Journal of Social Science, 2022)
The existence and contribution of Madrasas to Education In Indonesia there is no doubt, Madrasas are one of the concerns of Muslims for the importance of developing quality human resources through Islamic-based education. That the conditions of learning and management in Madrasahs still need monitoring, guidance and assistance in implementing national education standards. This needs to be done because people still doubt the quality of their learning. Madrasah principals must continue to improve their competence in order to carry out their duties and functions both academically and managerially in madrasas through regular and continuous professional development activities. In this research method using descriptive qualitative research methods, the purpose of this study is to determine the extent to which school principals in the Madrasah environment of the Jakarta area office with critical analysis because there are still many assumptions about the community that madrasas are often considered. Educational institutions whose quality is below other public schools. Therefore, madrasas still cannot be used as the main choice in learning.